2006
DOI: 10.1007/s00220-006-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Gap and Exponential Decay of Correlations

Abstract: We study the relation between the spectral gap above the ground state and the decay of the correlations in the ground state in quantum spin and fermion systems with short-range interactions on a wide class of lattices. We prove that, if two observables anticommute with each other at large distance, then the nonvanishing spectral gap implies exponential decay of the corresponding correlation. When two observables commute with each other at large distance, the connected correlation function decays exponentially … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
859
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(891 citation statements)
references
References 22 publications
26
859
5
1
Order By: Relevance
“…The next theorem is a Lieb-Robinson bound for such finite range Hamiltonians, similar to those proven for many-body Hamiltonians [8][9][10][11]. This result is also similar to results on the decay of entries of smooth functions of matrices proven in [12,13].…”
Section: Reduction To Block Tridiagonal Problemsupporting
confidence: 79%
“…The next theorem is a Lieb-Robinson bound for such finite range Hamiltonians, similar to those proven for many-body Hamiltonians [8][9][10][11]. This result is also similar to results on the decay of entries of smooth functions of matrices proven in [12,13].…”
Section: Reduction To Block Tridiagonal Problemsupporting
confidence: 79%
“…Indeed, Hastings and Koma proved this [77] for general short-range interacting spin systems. In contrast, recent theoretical studies have found that long-range interacting systems can have algebraically decaying correlation functions despite the existence of a gap [62,63,65].…”
Section: Role Of Dipolar Interactionsmentioning
confidence: 84%
“…Theorem 4 (Clustering of correlations in unique ground states [31,43]). Let H ∈ A(H) be a local Hamiltonian with a unique ground state ψ and a spectral gap ∆E > 0 and X, Y ⊂ V .…”
Section: Static Properties Derived From Lieb-robinson Boundsmentioning
confidence: 99%
“…Outside the space time cone defined by this speed, any signal is typically exponentially suppressed in the distance. The results of Lieb and Robinson, originally derived in the setting of translation invariant 1D spin systems with short range, or exponentially decaying interactions [38] have since been tightened [27,43] and extended to more general graphs [31,47] and to interactions decaying only polynomially with the distance, both, for spin systems [44] and fermionic systems [31] (see also Ref. [45] for a review).…”
Section: Introductionmentioning
confidence: 99%